Análise de transmissão 4x4 aplicada em um modelo 4x2 baja sae - Medeiros, Ruthenio Severo de (Universidade Federal Rural do Semi-Árido, 2018)
A transmission box is needed in a Baja vehicle due to the objective of the competitions organized by the SAE, in which the prototypes must undergo different obstacles. A main purpose of a transmission system is to increase the torque for the vehicle's drive axle when compared to that available on the output shaft of the engine. The objective of this work is to describe the design of a 4x4 transmission set to be applied in the Caraubaja SAE team of UFERSA, Caraúbas Campus. For the realization of the project a flow chart was used, which includes from the theoretical part, as definition of the problem for the teams until the definition of design of the project. The search for teams in the Baja SAE competitions for a good score in the traction and speed races has been a challenge. Finding an ideal curve to meet these requirements, has motivated the teams to carry out and idealize several types of projects, some even daring, being at the discretion of the judges a greater attention and leaving the doubt of the true viability of the project. In this work, the 4x4 transmission project will enable the traction and speed requirements with only one reduction gear ratio.
Monografia
Keywords: Transmissão 4x4; Caixa de redução; Tração; Velocidade; ENGENHARIAS::ENGENHARIA MECANICA